2022
DOI: 10.1097/mcc.0000000000001010
|View full text |Cite
|
Sign up to set email alerts
|

Home oxygen monitoring and therapy: learning from the pandemic

Abstract: Purpose of review Home oxygen monitoring and therapy have been increasingly used in the management of patients with chronic diseases. The COVID-19 pandemic has prompted the rapid uptake of remote monitoring programmes to support people with COVID-19 at home. This review discusses the recent evidence and learning in home oxygen monitoring and therapy from the pandemic. Recent findings Many home oxygen monitoring programmes were established around the world during the pandemic, mostly in high-income countries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 55 publications
(82 reference statements)
0
1
0
Order By: Relevance
“…There is limited pre-existing evidence for the effectiveness of pulse oximetry in health outcomes in patients with COVID-19 27. A previous evaluation of the COVID-19 pulse oximetry pilot programme in four sites in England found that none of those under 65 years and without long-term conditions died during the study, suggesting there were no safety concerns in lower-risk patients, but without a control group to compare differences in clinical outcomes 11.…”
Section: Discussionmentioning
confidence: 99%
“…There is limited pre-existing evidence for the effectiveness of pulse oximetry in health outcomes in patients with COVID-19 27. A previous evaluation of the COVID-19 pulse oximetry pilot programme in four sites in England found that none of those under 65 years and without long-term conditions died during the study, suggesting there were no safety concerns in lower-risk patients, but without a control group to compare differences in clinical outcomes 11.…”
Section: Discussionmentioning
confidence: 99%